The usefulness of the criminal compliance programs to the companies that operate in Peru - Reaño Peschiera, José Leandro (2015)
As a consequence of the 2007 financial crisis, companies have been focusing on managing the risks of normative infringement as an integral part of the notion of a business risk. This practice is encouraged by the implementation of normative with cross-border effects and reach, as well as by the growing internal regulations of autonomous criminal liability of corporate bodies systems.In the context of the circumstances described, in the present article the author analyzes: (i) the practical performance of the Criminal Compliance programs; (ii) their minimum content to exonerate or mitigate the criminal liability of the corporate bodies involved in a crime or offence; and, (iii) the challenges for the lawyer specialized in Criminal Law that this new approach of criminal preventingcounseling enforces.